1997
DOI: 10.1177/156482659701800107
|View full text |Cite
|
Sign up to set email alerts
|

Sources and Forms of Iron in Nigerian Foods and Effects of Processing on Availability

Abstract: The average diet in most developing countries, including Nigeria, is predominantly plant based. Cereals, legumes, tubers, and vegetables are the main food types. Although most of these food items have considerable iron, its low bioavailability is one of the factors accounting for the high incidence of iron-deficiency anaemia. The traditional processing procedures, fermentation and germination, improved the chemical and bioavailable iron in the foods studied. Techniques of measuring iron availability in vitro a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
3
4
0
Order By: Relevance
“…This higher amount of iron in these soup samples might be due to combinations of meats, fish, and other ingredients added to the soups. This corresponds to earlier reports that most Nigerian natural foods are rich in iron (Latunde‐Dada ). Openheimer () reported that iron deficiency was extremely common in the developing world, with <50% of the world's population having some degree of deficient iron status based on a wide variety of tests.…”
Section: Resultssupporting
confidence: 91%
“…This higher amount of iron in these soup samples might be due to combinations of meats, fish, and other ingredients added to the soups. This corresponds to earlier reports that most Nigerian natural foods are rich in iron (Latunde‐Dada ). Openheimer () reported that iron deficiency was extremely common in the developing world, with <50% of the world's population having some degree of deficient iron status based on a wide variety of tests.…”
Section: Resultssupporting
confidence: 91%
“…The iron contents of the diets ranged from 5.62mg/100g in "Akidi" to 1.11mg/100g in "Akara-Igboro" which were almost similar in comparison to those reported by Amadi [15] on some traditional diets of Southern Nigeria that ranged from 0.21ppm to 6.03mg/100g. The recommended daily allowance for iron is 10mg/day and 15mg/day for men and women respectively which suggest that the selected food can meet the daily dietary requirements for iron [39].This concurs to previous reports that most indigenous foods in Nigeria are rich in iron [45]. Iron deficiency is highly prevalent in most developing countries [46].…”
Section: Resultssupporting
confidence: 85%
“…High level of Iron in the soups might probably due to the ingredients and inclusion of meat which is a source of iron (Onabanjo and Oguntona, 2003). This corresponds to earlier reports that most Nigerian natural foods are rich in iron (Latunde-Dada, 1997). Openheimer (2000) reported that Iron deficiency was extremely common in the developing world, with less than 50 % of the world's population having some degree of deficient iron status based on a wide variety of tests.…”
Section: Effect Of Storage Period On the Mineral Compositions Of Freesupporting
confidence: 88%